2019
DOI: 10.1108/jcp-04-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Embedding third sector psychology services within the probation environment: an alternative to MHTRs

Abstract: Purpose The use of mental health treatment requirements (MHTRs) has not proven to be successful at meeting the mental health needs of the probation population in the UK, largely through underuse of the requirement or lack of available services. The paper aims to discuss this issue. Design/methodology/approach This paper investigates a method of meeting those needs without the use of MHTRs by embedding third sector services within the probation environment. Findings Results indicate a significant impact aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In addition, we identified four outcome studies (Callender, 2021; Fowler et al, 2020; Long et al, 2018; Newbury-Birch et al, 2014). Three of these papers relate to the use of Mental Health Treatment Requirements (MHTRs), which can be recommended by the courts, but despite the high prevalence of mental illness in the probation population have rarely been used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we identified four outcome studies (Callender, 2021; Fowler et al, 2020; Long et al, 2018; Newbury-Birch et al, 2014). Three of these papers relate to the use of Mental Health Treatment Requirements (MHTRs), which can be recommended by the courts, but despite the high prevalence of mental illness in the probation population have rarely been used.…”
Section: Resultsmentioning
confidence: 99%
“…Second, Fowler et al (2020) conducted a follow-up to this pilot after a full service had been commissioned. The K6 replaced the K10 as the initial screening tool, and the referral route was extended so that Probation Officers could directly refer those scoring 13+ to the service, rather than needing an MHTR to be recommended by the court.…”
Section: Outcome Studiesmentioning
confidence: 99%
“…In a unique study by Fowler et al (2019), all clients supervised by the Probation Service in London, were screened at assessment stage for mental health problems. A subgroup of 569 clients were identified and referred onwards to a specialist mental health service.…”
Section: International Experiencementioning
confidence: 99%
“…Fowler et al (2019) reported that a key issue related to client engagement with Mental Health Services was instability of housing/accommodation. This is consistent with Maslow’s theory of hierarchy of need (Maslow, 1943).…”
Section: International Experiencementioning
confidence: 99%
See 1 more Smart Citation